ANOMIE SOSIAL PADA REMAJA (STUDI TENTANG PERILAKU ADAPTIF DAN TEKANAN SOSIAL PADA MANTAN NARAPIDANA REMAJA DI KOTA PAYAKUMBUH - Akbar, Saputra Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
which also very big from process modernize is the increasing of criminality number. Badness and criminality expand along with progress of epoch , criminality and badness expand in line with increasing resident [him/ it] , urbanization and pembangunan,modernisasi . that thing happened because [in] urban of indisposed tight emulation even [is] thereby said that [by] growth of town [is] always accompanied with growth of criminality quantity and quality. As a result growth of that situation generate disquiet of society and government of town. ( 1) How social pressure which accepted by former adolescent convict of society? ( 2) how behavior of adaptation of[is former adolescent convict in the middle of society?. Intention of this research to know social pressure which accepted by former adolescent convict [in] society, and to know behavior of adaptation of[is former adolescent convict [in] society. this research represent descriptive research with approach qualitative. Subjek in this research [is] the former convict institute special construction [of] class child of II sub-province fifty town counted 6 informan by 12 last supporter informan [in] using technique of purposive sampling, to collect data [at] this research [is] used [by] circumstantial interview, observation, and documentation. Pursuant to result of research above earning [in] concluding that ( 1) There are 3 social pressure which [in] accepting by former convict after exit of special construction institute [of] child of klas II extract foreland, the tkanan that is social pressure of family, social pressure of residence society and social pressure in economic activity, but the pressure there [is] which [in] accepting to duplicate even the pressure [in] accepting the overall of by former convict after exit of institute ( 2) some of the informan also accept pressure of residence society environment, making the former narapidan get bad view of its residence environment which finally cause the the informan have me me [to] digress again after exit of construction institute, here also [in] finding of pressure in economic activity where former the convict cannot x'self menyeseuaikan in requirement of economics in the middle of society, [the] mentioned happened because [do] not get work [in] its residence environment and education the broken after exit of construction institute. : ( 3) have my Me [to] follow the way of and order to reach the target of which [in] determining [in] society ( Konformitas have), me me [to] by wrong according to society but reach the target of which [in] accepting society ( Inovasi) and behavior wearing the way of which [is] prohibited and [do] not sesui with [in] determining society and yield behavior which outside norm and value in society in the form of pembrontakan of attitude ( Rebellion)